2020
DOI: 10.26565/2312-4334-2020-4-09
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Bulk and Single-Layer MoS2 Using ab Initio DFT: Application of Spin-Orbit Coupling (SOC) Parameters

Abstract: Two dimensional (2D) materials are currently gaining a lot of interest due to excellent properties that are different from their bulk structures. Single and few-layered of Transition metal dichalcogenides (TMDCs) have a bandgap that ranges between 1-2 eV, which is used for FET devices or any optoelectronic devices. Within TMDCs, a ton of consideration is focused on Molybdenum Disulfide (MoS2) because of its promising band gap-tuning and transition between direct to indirect bandgap properties relies upon its t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Using this method, which considers the core and valence electrons to be self-consistent in a full-potential treatment, the authors reported the energy band gaps of 1.23 and 1.7 eV for MoS 2 bulk and monolayer, respectively. In another interesting work, Gyan et al 16 studied MoS 2 energy band gaps by considering in their approach the plane-wave pseudopotential approximation within the LDA method and spin–orbit coupling within the generalized gradient approximation (GGA) method. The authors reported an indirect energy band gap in the range of 1.17–1.71 eV for bulk system and 1.6–1.71 eV for monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, which considers the core and valence electrons to be self-consistent in a full-potential treatment, the authors reported the energy band gaps of 1.23 and 1.7 eV for MoS 2 bulk and monolayer, respectively. In another interesting work, Gyan et al 16 studied MoS 2 energy band gaps by considering in their approach the plane-wave pseudopotential approximation within the LDA method and spin–orbit coupling within the generalized gradient approximation (GGA) method. The authors reported an indirect energy band gap in the range of 1.17–1.71 eV for bulk system and 1.6–1.71 eV for monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, similar band splitting can also be observed at the PBE level, as presented in Figure S5. This distinct band splitting suggests that BiSbX 3 (X = S, Se) monolayers may have potential applications in spintronics and valleytronics . In addition, the band gap values of these two monolayers calculated at different levels are summarized in Table S2.…”
mentioning
confidence: 99%
“…This distinct band splitting suggests that BiSbX 3 (X = S, Se) monolayers may have potential applications in spintronics and valleytronics. 58 In addition, the band gap values of these two monolayers calculated at different levels are summarized in Table S2. To further explore the contribution of each element in these two monolayers, their projected band structure and projected density of states (PDOS) calculated at the HSE level with a consideration of the SOC are depicted in Figure 5.…”
mentioning
confidence: 99%